Avoid Becoming a Dinosaur that is Important in Change Management: Dinosaur Syndrome - Yeşilyurt, Özgür (Muş Alparslan Üniversitesi, 2021)
Change in business organizations may emerge due to both economic and environmental conditions. Another condition that necessitates change is technological developments. The subject of change is sometimes tried to be prevented by being exposed to the employees'resistance. This study aims to examine the conceptual framework of the dinosaur syndrome in the context of change management. We thought that employees'dislike of change and innovations and attempt to prevent them leads them to dinosaur syndrome. Dinosaur syndrome refers to the resistance to change that can be seen in business organizations along with individuals. It should not be forgotten that the basis of the dinosaur syndrome seen in business organizations is also the employees. Dinosaur syndrome emerges in three stages. The first stage consists of encountering, confrontation, and disharmony, and the second stage of resistance to change and rejection of change. And finally, the third stage consists of clumsiness-downsizing, extinction, transformation into another organization. In conclusion, the success of change depends on placing the change as a lifestyle in the business culture, including employees in the change processes as much as possible, and their participative management approach.

İşletmelerde değişim gerek ekonomik gerekse çevresel koşullardan dolayı ortaya çıkabilmektedir. Değişimi zorunlu kılan diğer bir koşul da teknolojik gelişmelerdir. Değişim konusu bazen çalışanların direncine maruz kalarak engellenemeye çalışılmaktadır. Bu çalışmanın amacı değişim yönetimi bağlamında dinozor sendromunun kavramsal çerçevesinin irdelenmesidir. Çalışanların değişimi ve yenilikleri sevmemesi ve engellemeye çalışması durumunun çalışanları dinozor sendromuna yönlendirdiği düşünülmektedir. Dinozor sendromu bireylerde görüldüğü gibi organizasyonlarda da görülebilen değişim karşısındaki direnci ifade etmektedir. Organizasyonlarda görülen dinozor sendromunun temelinde de yine çalışanların olduğu unutulmamalıdır. Dinozor sendromu üç evrede ortaya çıkmaktadır. Birinci evre; karşılaşma, yüzleşme ve uyumsuzluk, ikinci evre; değişim karşısında direnme ve değişimi reddetme, üçüncü evre ise; hantallaşma-küçülme, yok olma, bir başka örgüte dönüşümdür. Sonuç olarak; değişimin başarısı değişimin bir yaşam tarzı olarak işletme kültürü içerisine yerleştirilmesine, çalışanların değişim süreçlerine mümkün olduğunca dahil edilmelerine ve katılımcı yönetim anlayışına sahip olmalarına bağlıdır.
Değişim Yönetiminde Önemli Olan Dinozorlaşmamak: Dinozor Sendromu
anemon
Keywords: Change in Business; Change Management; Dinosaur Syndrome; Innovation Management; İşletmelerde Değişim; Değişim Yönetimi; Dinozor Sendromu; Yenilik Yönetimi